A Comprehensive Review on Nanoparticle Classification and Synthesis Methods - Anis J, Kazi; Shafi, Dr. Sameer; Harsh, Waghmare; Sameena, Shaikh; Punam, Ritthe; Muktai, Rudrurkar; Sneha, Patil; Imran, Shaikh (Asian Journal of Pharmaceutical Research and Development, 2023)
Nanoparticles synthesis and the study of their size and properties are important in medicine as well as biological fields nanotechnology using nanoparticles such as metals, semiconductors and metal oxides are of great interest for a wide of variety of applications in the field of data, energy, environmental and medical tools due to their unique or improved properties. Current review focus on nanoparticle, types, characterization and most advanced application related to nanotechnology.It has the potential to revolutionize a series of medical and biotechnology tools and procedures so that they are portable, cheaper, safer, and easier to administer. They were synthesized by various methods for research and commercial uses which are classified into three types-chemical, physical and mechanical processes which had sawn a vast improvement. It plays a major role in the development of innovative methods to produce new products to suitable existing production equipment and to reformulate new material and chemicals with improved performance resulting in less consumption of energy and material and reduce harm to the environment as well as environmental remediation.